Kesadaran Masyarakat dalam Menunaikan Zakat di Lazismu PDM Sukoharjo Studi Analisis Tafsir Surah At Taubah Ayat 103 - Mukhlis Ardi Pratama; Ainur Rhain (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze public awareness in fulfilling zakat obligations at Lazismu PDM Sukoharjo by examining the influence of zakat literacy, trust in zakat management institutions, and religious understanding based on the interpretation of Surah At-Taubah verse 103. The verse emphasizes that zakat is not merely a financial obligation, but also a means of spiritual and moral purification with deep social dimensions. This research employs a descriptive qualitative method, utilizing data collection techniques such as literature review, in-depth interviews, and direct observation. The findings reveal that zakat awareness among the people of Sukoharjo remains relatively low, as reflected in the zakat collection realization which only reached 2.90% of the total potential of IDR 48.7 billion. Low levels of zakat literacy, limited theological comprehension, and lack of trust in zakat institutions are the primary factors influencing muzaki compliance. Conversely, Lazismu PDM Sukoharjo has taken strategic initiatives through educational programs rooted in Qur’anic interpretation, financial transparency, digital zakat services (QRIS, e-wallet, SIM), social media fundraising, and economic empowerment of zakat recipients through productive zakat schemes. This study affirms that enhancing zakat awareness requires not only formal and structural approaches but also integrated spiritual and cultural engagement. The synergy between religious understanding, zakat literacy, technological innovation, and institutional credibility serves as the key to establishing an inclusive, sustainable, and impactful zakat management system for empowering the Muslim community.